Reduction of Doxorubicin-Induced Cardiotoxicity by Co-Administration of Smart Liposomal Doxorubicin and Free Quercetin: In Vitro and In Vivo Studies - Hamidreza Dorostkar; Bibi Fatemeh Haghiralsadat; Mahdie Hemati; Fatemeh Safari; Azam Hassanpour; Seyed Morteza Naghib; Mohammad Hossein Roozbahani; M. R. Mozafari; Ali Moradi (Pharmaceutics, 2023)
Doxorubicin is one of the most effective chemotherapeutic agents; however, it has various side effects, such as cardiotoxicity. Therefore, novel methods are needed to reduce its adverse effects. Quercetin is a natural flavonoid with many biological activities. Liposomes are lipid-based carriers widely used in medicine for drug delivery. In this study, liposomal doxorubicin with favorable characteristics was designed and synthesized by the thin-film method, and its physicochemical properties were investigated by different laboratory techniques. Then, the impact of the carrier, empty liposomes, free doxorubicin, liposomal doxorubicin, and quercetin were analyzed in animal models. To evaluate the interventions, measurements of cardiac enzymes, oxidative stress and antioxidant markers, and protein expression were performed, as well as histopathological studies. Additionally, cytotoxicity assay and cellular uptake were carried out on H9c2 cells. The mean size of the designed liposomes was 98.8 nm, and the encapsulation efficiency (EE%) was about 85%. The designed liposomes were anionic and pH-sensitive and had a controlled release pattern with excellent stability. Co-administration of liposomal doxorubicin with free quercetin to rats led to decreased weight loss, creatine kinase (CK-MB), lactate dehydrogenase (LDH), and malondialdehyde (MDA), while it increased the activity of glutathione peroxidase, catalase, and superoxide dismutase enzymes in their left ventricles. Additionally, it changed the expression of NOX1, Rac1, Rac1-GTP, SIRT3, and Bcl-2 proteins, and caused tissue injury and cell cytotoxicity. Our data showed that interventions can increase antioxidant capacity, reduce oxidative stress and apoptosis in heart tissue, and lead to fewer complications. Overall, the use of liposomal doxorubicin alone or the co-administration of free doxorubicin with free quercetin showed promising results.